Material Composition Design and Anticracking Performance Evaluation of Asphalt Rubber Stress-Absorbing Membrane Interlayer (AR-SAMI) - Ke Zhang; Zhengqi Zhang; Yaofei Luo (Advances in Materials Science and Engineering)
To promote the application of the asphalt rubber stress-absorbing membrane interlayer (AR-SAMI), the material composition design and the evaluation of antireflective cracking effect of AR-SAMI need to be studied. In this paper, conventional asphalt tests, dynamic shear rheometer (DSR) test, and fatigue cracking test were conducted to evaluate the high and low temperature performance, elastic recovery property, and antifatigue performance of SK90# raw asphalt, asphalt rubber, and SBS-modified asphalt. The AR-SAMI’s material composition design method based on the interlaminar shear strength was put forward. The influence of the asphalt application rate and aggregate application rate on interlaminar shear strength was also discussed to determine the optimum material composition. The fatigue cracking test was designed based on the Hamburg rutting instrument, and the cracking resistance of AR-SAMI was analyzed. The results indicate that asphalt rubber is the suitable binder for SAMI. The application rates of asphalt and aggregate have significant impact on the interlaminar shear strength of AR-SAMI. The optimum binder application rate of asphalt rubber and aggregate application rate are 2.2 kg/m2 and 14 kg/m2, respectively, for AR-SAMI. The fatigue cracking life and fatigue fracture life of composite specimens increase obviously after AR-SAMI is paved. The increasing range of fatigue life because of the use of AR-SAMI is up to 30% under the dry condition of 15°C. The decreasing range of fatigue life caused by water reaches as high as 50%. The fatigue life falls sharply when the temperature increases from 15°C–25°C to 35°C–45°C.